Is medical home care adequacy associated with educational service use in children and youth with autism spectrum disorder (ASD)? - Sabrin Rizk; Emmanuel Ngui; Teal W. Benevides; Victoria A. Moerchen; Mary Khetani; Kris Barnekow (BMC, 2023)
Abstract Background The American Academy of Pediatrics (AAP) recommends medical home care for children and youth with autism spectrum disorder (ASD) for health needs. Children and youth with ASD also receive educational services for cognitive, social, and behavioral needs. We measured whether inadequate medical home care was significantly associated with current educational service use, controlling for sociodemographic factors. Methods We analyzed the 2016/2017 National Survey of Children's Health (NSCH) on 1,248 children and youth with ASD ages 1-17. Inadequate medical home care was operationalized as negative or missing responses to at least one medical home component. Educational service use was defined as current service use under individualized family service plans (IFSP) and individualized education programs (IEP). Results Inadequate medical home care was significantly associated with higher likelihood of current educational service use (aOR = 1.95, 95% CI [1.10, 3.44], p = 0.03). After adjustment, older children (aOR = 0.91, 95% CI [0.84, 0.99], p = 0.03), lower maternal health (aOR = 0.52, 95% CI [0.29, 0.94], p = 0.03), and children without other special health care factors (aOR = 0.38, 95% CI [0.17-0.85], p = 0.02) had significantly lower odds of current educational service use. Conclusions Inadequate medical home care yielded higher odds of current educational service use. Child's age, maternal health, and lack of other special health care factors were associated with lower odds of current educational service use. Future research should examine medical home care defined in the NSCH and improving educational service use via medical home care.